ANALISIS WAKTU PERJALANAN BANJIR SUNGAI BENGAWAN SOLO - , Muhammad Arwan F.A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Almost every year, flood phenomenons occur in Bengawan Solo watershed. The length of Bengawan Solo river which reached about 600 kms causing the water travel from upstream to downstream in Bengawan Solo river takes hours to days. Therefore, the information of flood travel time from upstream to downstream is important to know for mitigating floods. There are two analysis in this research, hydrological and hydraulics analysis. Hydrological analysis was conducted in order to transform rain into discharge in tributaries. Hydraulics analysis is done by simulation using HEC-RAS software version 4.1.0. Simulations are carried out with three scenarios based on three cases of flooding. The flood flow derive from the Upper Solo River, Madiun River, and from both. The simulation shows significant differences of flood travel time between these three simulation scenarios. For example, the flood travel time of Bengawan Solo River from Colo Weir (upstream) to Floodway Junction (downstream) which is about 400 miles was 61 hours in Scenario 1, 60 hours in Scenario 2, and 50 hours in Scenario 3.